Every Man a Tiger - Clancy, Tom, 1947-2013 and Horner, Chuck, 1936- (London Pan Books, 2001)
Launching the "Tom Clancy's Commanders" series, this is General Chuck Horner's account of the air war over the Persian Gulf during Operations Desert Shield and Desert Storm. He was in command of the US and Allied air forces at this time.
Include Index
Keywords: Persian Gulf War (1991) -- United States -- Horner, Chuck, 1936-